Correlates of Non-suicidal Self-Injury and Suicide Attempts in Bulimic Spectrum Disorders - Gómez-Expósito, Alexandra; Wolz, Ines; Fagundo, Ana B.; Granero, Roser; Steward, Trevor; Jiménez-Murcia, Susana; Agüera, Zaida; Fernández-Aranda, Fernando (Frontiers in Psychology, 2016)
Objective: The aim of this study was to examine the implication of personality, impulsivity, and emotion regulation difficulties in patients with a bulimic-spectrum disorder (BSD) and suicide attempts (SA), BSD patients with non-suicidal self-injury (NSSI), and BSD patients without these behaviors. Method: 122 female adult BSD patients were assessed using self-report questionnaires. Patients were clustered post-hoc into three groups depending on whether they presented BSD without NSSI or SA (BSD), BSD with lifetime NSSI (BSD+NSSI) or BSD with lifetime SA (BSD+SA). Results: The BSD+NSSI and BSD+SA groups presented more emotion regulation difficulties, more eating and general psychopathology, and increased reward dependence in comparison with the BSD group. In addition, BSD+SA patients specifically showed problems with impulse control, while also presenting higher impulsivity than both the BSD and BSD+NSSI groups. No differences in impulsivity between the BSD and BSD+NSSI groups were found. Conclusions: The results show that BSD + NSSI and BSD+SA share a common profile characterized by difficulties in emotion regulation and low reward dependence, but differ in impulsivity and cooperativeness. This suggests that self-injury, in patients without a history of suicide attempts (i.e. BSD+NSSI), may have a regulatory role rather than being due to impulsivity.